POSITION AS MAIN FACTOR OF FORMING AND DEVELOPMENT OF CREATIVE PERSONALITY (Pedagogy of Higher and Secondary Education, 2022)
The features of forming and development of composition capabilities (special composition abilities and skills) as determining criteria of effectiveness in preparation of future teacher of fine art are considered in the article. An author attaches important significance to “Composition” as educational object which directly influences on development of creative capabilities of student.